TEACHING ENGLISH LANGUAGE TO THE BEGINNERS - Clary Sada; Irfan Agung Wiranto (Jurnal Visi Ilmu Pendidikan)
his  study  aims  to  find  out  the  appropriate  method  to  teach English  to  the  beginners.  Also,  the  finding  of  this  research  is  for publication in the journal. This study is conducted by using online qualitative  survey  technique.  The  subjects  of  this  study  were teachers  who  teach  English  for  beginners  in  Pontianak  and  its surrounding.  The  data  were  collected  by  a  set  of  close-ended statements in an online questionnaire and also an online interview. The  findings  showed  that  there  were  various  methods  that  can  be applied  in  teaching  English  to  the  beginners,  and  those  methods depend  on  the  students’  learning  style.  Since  students’  learning style are different from one to another, the teachers may use various methods  in  their  classroom.  However,  even  when  the  methods  are various,  not  every  method  is  effective  in  teaching  English  to  the beginners.  Therefore,  the  teachers  need  to  choose  the  appropriate methods carefully in teaching English to the beginners. Keywords:  Teaching  English,  Teaching  Beginners,  English Language Teaching